Review of Legal Protection of Acts of Violence against Children in Boarding Schools according to Positive Law and Islamic Law - Dinda Kustarin Salekhah; R Rizka (Proceeding International Conference Restructuring and Transforming Law, 2024)
Children are a great trust that must be cared for and guarded from various forms of discrimination. The boarding school is the party that is responsible for providing this care shortly after the child's parents hand over their care, so that all forms of discrimination such as violence are very contrary to this noble task. Both positive law and Islamic law both view violence against children in boarding schools as a reprehensible act that violates the norm of nobility. This research aims to: 1) Know how the efforts of boarding school in preventing and handling cases of violence in pesantren; and 2) Know how the comparison of legal protection against cases of violence in boarding school according to positive law and Islamic law. Through normative juridical research with a statutory and comparative approach whose data is obtained through literature studies of primary, secondary, and tertiary legal materials, the author finds that legal protection of child victims of violence in Islamic boarding schools is urgent. Its implementation can be realized through penal and non-penal efforts. Islam also views such legal protection as mandatory because it is part of Islamic law. The conclusion that can be drawn is that the protection of child victims of violence in Islamic boarding schools is something that is upheld by positive law and Islamic law which requires active cooperation from various parties so that prosperous justice can be achieved by taking into account the best interests of the child.